ENDOCRINE GLANDS AND DISEASES IN THE CIS - Xasanova Madina Qaxramon qizi; Abduraxmonova Lobar Nuriddin qizi (Galaxy International Interdisciplinary Research Journal, 2022)
A plethora of hormones regulate many of the body’s functions, including growth and development, metabolism, electrolyte balances, and reproduction. Numerous glands throughout the body produce hormones. The hypothalamus produces several releasing and inhibiting hormones that act on the pituitary gland, stimulating the release of pituitary hormones. Of the pituitary hormones, several act on other glands located in various regions of the body, whereas other pituitary hormones directly affect their target organs. Other hormone-producing glands throughout the body include the adrenal glands, which primarily produce cortisol; the gonads (i.e., ovaries and testes), which produce sex hormones; the thyroid, which produces thyroid hormone; the parathyroid, which produces parathyroid hormone; and the pancreas, which produces insulin and glucagon. Many of these hormones are part of regulatory hormonal cascades involving a hypothalamic hormone, one or more pituitary hormones, and one or more target gland hormones.